Hubungan Antara Lama Menderita Diabetes Melitus Tipe 2 Dengan Terjadinya Neuropati Sensorik Diabetik Di RSUD Salatiga - Lestari, Dwi, dr. Nur Hidayat, Sp. PD, dr. Erika Diana Risanti (2015)
Background: Type 2 Diabetes Mellitus occurs as a result of the body's resistance to the effects of insulin produced by the pancreatic cells. Type 2 Diabetes Mellitus is the largest case in Indonesia. Having diabetes mellitus for a long time and uncontrolled caused various complications such as diabetic sensory neuropathy. Diabetic sensory neuropathy is a disorder of the peripheral nervous system. Persistent hyperglycemia suspected as risk factor for diabetic sensory neuropathy. Objective: The purpose of this study to determine the relationship between the length of time of suffering Type 2 Diabetes and Diabetic Sensory Neuropathy occurrence. Methods: This study used a cross-sectional design. Sampling using purposive sampling method with a sample of 35 patients with type 2 diabetes mellitus in RSUD of Salatiga. The instrument used in this study was a questionnaire. Data is analize using Chi-Square test bivariate. Results: The results show X2 = 20.896 (<X2 table = 3.841) and p value = 0.000 (<α = 0.05) means there is a significant relationship between length of diabetes mellitus suffering time with diabetic sensory neuropathy occurrence. Long suffered from diabetes for less than ten years with the highest proportion of sensory neuropathy is at 51.42%. Conclusion: There is relationship between the length of time of suffering type 2 diabetes mellitus and diabetic sensory neuropathy in RSUD Salatiga.